Highly durable super hydrophobic glass and preparation method thereof
By constructing a double-scale rough structure and a double interpenetrating network structure on the glass surface, the problem of insufficient wear resistance of existing superhydrophobic materials is solved, and the preparation of high-durability superhydrophobic glass is realized, with good wear resistance and hydrophobicity.
Patent Information
- Application Number
- CN202411348444.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The wear resistance of existing superhydrophobic materials is insufficient and prone to aging, making it difficult to maintain efficient hydrophobic properties for a long time in practical applications.
Using the synergistic effect of a double-scale rough structure and a double interpenetrating network structure, a high-durable superhydrophobic glass is formed by constructing the combination of carbon nanotube/polyurethane solution and carbon fiber microparticles on the glass surface. The method includes formulating an epoxy resin binder and a carbon nanotube/polyurethane solution, respectively coated on the glass surface, and curing by drying to form a stable coating structure.
The wear resistance and hydrophobic properties of the glass surface are significantly improved, the contact angle can reach 159.5°, and it is maintained above 146° in the 5000g sand drop experiment, proving its high durability.
Smart Images

Figure CN118851591B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass surface hydrophobic treatment, and in particular to highly durable super hydrophobic glass and a preparation method thereof. Background Art
[0002] The super-hydrophobic surface comes from bionics. It is observed that water droplets roll off the surface of lotus leaves, which makes it have self-cleaning ability. Its surface has a columnar nano-scale protrusion structure, and at the same time has a low surface energy material. When in contact with water droplets, there will be a large contact angle, which makes it very easy for water droplets to roll off the surface of lotus leaves. Through summary, it is concluded that the surface of lotus leaves has super-hydrophobic properties. Super-hydrophobicity refers to the contact angle of water droplets on the surface of the material being greater than 150 °. Generally, the material can be made super-hydrophobic by constructing a micro-nano rough structure, so that the water droplets and the surface of the material form an air film and strengthen the low surface energy characteristics of the material. Super-hydrophobic materials are widely used in life and production, but like the surface of lotus leaves, the surface of the artificially constructed micro-nano rough structure is easy to wear and damage, and is easy to age. This shows that super-hydrophobic materials still have certain shortcomings, and further research is needed to improve the wear resistance of super-hydrophobic materials. Summary of the invention
[0003] The technical problem to be solved by the present invention is: to overcome the shortcomings of the prior art, to provide highly durable super-hydrophobic glass and a preparation method thereof, to utilize the synergistic effect of a dual-scale rough structure and a dual interpenetrating network structure, to achieve passive anti-wear properties, and to improve the durability of the glass hydrophobic surface.
[0004] The technical solution of the present invention is:
[0005] In one aspect, the present invention provides a method for preparing a highly durable super-hydrophobic glass, comprising the following steps:
[0006] (1) Preparation of epoxy resin adhesive
[0007] Adding epoxy resin to an organic solvent and stirring until dissolved, adding a curing agent and stirring until dissolved to obtain an epoxy resin adhesive;
[0008] (2) Preparation of carbon nanotube / polyurethane solution
[0009] 1) Preparation of polyurethane prepolymer
[0010] Toluene diisocyanate (TDI) and hydroxyl-terminated liquid polybutadiene rubber (HTPB) are added to an organic solvent, prepolymerized at 60-80°C for 1-2 hours, and then cooled to room temperature to obtain a polyurethane prepolymer, wherein the mass ratio of the soft segment to the hard segment of the polyurethane prepolymer is 3:(1-2);
[0011] 2) Preparation of carbon nanotube / polyurethane solution
[0012] Adding carbon nanotubes to an organic solvent, and then adding the organic solvent to the polyurethane prepolymer prepared in step 1), mixing evenly, to obtain a carbon nanotube / polyurethane solution, wherein the mass ratio of the carbon nanotubes to the hard segment in the polyurethane prepolymer is (1-4):1;
[0013] (3) Preparation of highly durable superhydrophobic glass
[0014] a) Apply surfactant on the surface of the glass sheet;
[0015] b) brushing the epoxy resin adhesive prepared in step (1) on the surfactant;
[0016] c) using a micron-sized mesh screen to evenly disperse the carbon fiber micron particles on a glass sheet coated with an epoxy resin adhesive, and drying, wherein the thickness of the carbon fiber micron particles on the glass sheet is 0.2-0.4 mm;
[0017] d) spraying the carbon nanotube / polyurethane solution prepared in step (2) onto the carbon fiber micron particles to a thickness of 0.2-0.3 mm, and drying to obtain a highly durable super hydrophobic glass.
[0018] In the present invention, polyurethane is in a mutually cross-linked long chain form composed of soft segments and hard segments, and the radial size of carbon nanotubes is nanometer-level and the axial size is micrometer-level, and it is a hollow structure; by mixing and curing the polyurethane long chain prepolymer with the carbon nanotubes, the polyurethane chain can be wound around the wall of the carbon nanotubes, and the winding of the chain segments and the carbon nanotubes can significantly improve the stability of the coating structure, improve its mechanical strength, and thus improve the wear resistance of the coating.
[0019] Preferably, in step (1), the concentration of epoxy resin in the epoxy resin adhesive is 18-22 wt.%, and the concentration of curing agent is 1.6-2 wt.%.
[0020] Preferably, in step (1) and step (2), the organic solvent is ethyl acetate or ethanol, and the curing agent is tetraethylenepentamine or triethylenetetramine.
[0021] Preferably, in step a), the surfactant is KH550.
[0022] Preferably, in step a), the thickness of the surfactant applied on the glass sheet is 0.02-0.05 mm.
[0023] Preferably, in step b), the thickness of the epoxy resin adhesive applied on the glass sheet is 0.1-0.3 mm.
[0024] Preferably, in step c) and step d), the drying temperature is 60-80° C. and the drying time is 1-3 h.
[0025] On the other hand, the present invention provides a highly durable super hydrophobic glass, which is prepared by the above-mentioned method for preparing the highly durable super hydrophobic glass.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. When preparing highly durable super-hydrophobic glass, the present invention synthesizes polyurethane prepolymer, mixes with carbon nanotubes, and is coated on the glass surface and solidified, so that a double network interpenetrating structure of polyurethane and carbon nanotubes can be formed, and the roughness and wear resistance of nanometer scale can be improved, and the hydrophobic characteristics and durability of the glass surface are greatly improved. At the same time, the present invention utilizes the rough structure of nanometer and micron-sized constructed by carbon fiber micron particles and carbon nanotubes / polyurethane to realize double-scale rough structure, and the double-scale rough structure can greatly improve the wear resistance and hydrophobic characteristics of the hydrophobic surface of glass. Therefore, the present invention utilizes the synergistic effect of double-scale rough structure and double interpenetrating network structure, realizes passive anti-wear characteristics, and improves the durability of hydrophobic surface.
[0028] 2. The highly durable super-hydrophobic glass prepared by the present invention has good wear resistance and hydrophobicity. The optimal contact angle of the finished product can reach 159.5°. In the 5000g falling sand test, the contact angle can still be maintained above 146°. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Example 1 of the present invention.
[0030] Figure 2 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Example 1 of the present invention after passing a 5000g falling sand test.
[0031] Figure 3 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Example 2 of the present invention.
[0032] Figure 4 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Example 2 of the present invention after passing a 5000g falling sand test.
[0033] Figure 5 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Example 3 of the present invention.
[0034] Figure 6 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Example 3 of the present invention after passing a 5000g falling sand test.
[0035] Figure 7 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Example 4 of the present invention.
[0036] Figure 8This is a contact angle picture of the highly durable super hydrophobic glass prepared in Example 4 of the present invention after passing a 5000g falling sand test.
[0037] Fig. 9 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Comparative Example 1 of the present invention.
[0038] Fig.10 This is a contact angle picture of the highly durable super hydrophobic glass prepared in Comparative Example 1 of the present invention after passing a 5000g falling sand test.
[0039] Fig.11 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Comparative Example 2 of the present invention.
[0040] Fig.12 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Comparative Example 2 of the present invention after passing a 5000g falling sand test.
[0041] Fig.13 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Comparative Example 3 of the present invention.
[0042] Fig.14 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Comparative Example 3 of the present invention after passing a 5000g falling sand test.
[0043] Fig.15 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Comparative Example 4 of the present invention.
[0044] Fig.16 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Comparative Example 4 of the present invention after passing a 5000g falling sand test.
[0045] Fig.17 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Comparative Example 5 of the present invention.
[0046] Fig.18 This is a contact angle picture of the highly durable super hydrophobic glass prepared in Comparative Example 5 of the present invention after passing a 5000g falling sand test.
[0047] Fig.19 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Comparative Example 6 of the present invention.
[0048] Fig. 20 This is a contact angle picture of the highly durable super hydrophobic glass prepared in Comparative Example 6 of the present invention after passing a 5000g falling sand test.
[0049] Fig.21 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Comparative Example 7 of the present invention.
[0050] Fig. 22 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Comparative Example 7 of the present invention after passing a 5000g falling sand test.
[0051] Fig.23 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Comparative Example 8 of the present invention.
[0052] Fig.24 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Comparative Example 8 of the present invention after passing a 5000g falling sand test.
[0053] Fig.25 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Comparative Example 9 of the present invention.
[0054] Fig.26 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Comparative Example 9 of the present invention after passing a 5000g falling sand test.
[0055] Fig. 27 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Comparative Example 10 of the present invention.
[0056] Fig.28 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Comparative Example 10 of the present invention after passing a 5000g falling sand test.
[0057] Fig.29 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Comparative Example 11 of the present invention.
[0058] Fig.30 This is a contact angle picture of the highly durable super hydrophobic glass prepared in Comparative Example 11 of the present invention after passing a 5000g falling sand test.
[0059] Fig.31 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Comparative Example 12 of the present invention.
[0060] Fig.32 This is a contact angle picture of the highly durable super hydrophobic glass prepared in Comparative Example 12 of the present invention after passing a 5000g falling sand test.
[0061] Fig.33 This is a contact angle picture of the highly durable super-hydrophobic glass prepared in Comparative Example 13 of the present invention.
[0062] Fig.34 This is a contact angle picture of the highly durable super hydrophobic glass prepared in Comparative Example 13 of the present invention after passing a 5000g falling sand test. DETAILED DESCRIPTION
[0063] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0064] Example 1
[0065] The preparation method of the highly durable super hydrophobic glass of the present embodiment comprises the following steps:
[0066] (1) Preparation of 18wt.% epoxy resin adhesive
[0067] Add 1.8 parts of epoxy resin to 8.04 parts of ethyl acetate, stir until dissolved, then add 0.16 parts of tetraethylenepentamine, stir until completely dissolved to obtain epoxy resin adhesive, put it into a reagent bottle for later use;
[0068] (2) Preparation of carbon nanotube / polyurethane solution
[0069] 1) Preparation of polyurethane prepolymer
[0070] 1.05 parts of TDI and 3 parts of HTPB were added to 25.25 parts of ethyl acetate, stirred evenly, and put into a flask, and then the flask was placed in an oil bath and stirred at 60°C. After prepolymerization for 2 hours, the flask was taken out and cooled to room temperature to obtain a polyurethane prepolymer;
[0071] 2) Preparation of carbon nanotube / polyurethane solution
[0072] Add 1.05 parts of carbon nanotubes to 5.25 parts of ethyl acetate, stir evenly, and mix evenly with polyurethane prepolymer to obtain a carbon nanotube / polyurethane solution, which is placed in a reagent bottle for later use;
[0073] (3) Preparation of highly durable superhydrophobic glass
[0074] a) Apply KH550 on the surface of the glass sheet with a thickness of 0.02mm;
[0075] b) Apply epoxy resin adhesive with a thickness of 0.1mm;
[0076] c) Use a micron-sized mesh to evenly disperse carbon fiber micron particles on a glass sheet coated with epoxy resin adhesive to a thickness of 0.2 mm, and place in an oven at 60°C for 3 hours;
[0077] d) Spraying carbon nanotube / polyurethane solution on carbon fiber micron particles with a thickness of 0.2 mm, drying in an oven at 60° C. for 3 h, and obtaining highly durable super-hydrophobic glass.
[0078] The contact angle test was performed on the highly durable super hydrophobic glass prepared in this embodiment. Figure 1-2As shown, the measured contact angle is 150°. After the 5000g falling sand test, the contact angle is measured to be 146.2°.
[0079] Example 2
[0080] The preparation method of the highly durable super hydrophobic glass of the present embodiment comprises the following steps:
[0081] (1) Preparation of 20wt.% epoxy resin adhesive
[0082] Add 2 parts of epoxy resin to 7.82 parts of ethanol, stir until dissolved, then add 0.18 parts of triethylenetetramine, stir until completely dissolved to obtain epoxy resin adhesive, put it into a reagent bottle for later use;
[0083] (2) Preparation of carbon nanotube / polyurethane solution
[0084] 1) Preparation of polyurethane prepolymer
[0085] 1.05 parts of TDI and 2.1 parts of HTPB were added to 25.25 parts of ethanol, stirred evenly, and put into a flask, and then the flask was placed in an oil bath pot and stirred at 70°C. After the prepolymerization reaction for 1.5 hours, the flask was taken out and cooled to room temperature to obtain a polyurethane prepolymer;
[0086] 2) Preparation of carbon nanotube / polyurethane solution
[0087] Add 2.1 parts of carbon nanotubes to 10.5 parts of ethanol, stir evenly, and mix evenly with polyurethane prepolymer to obtain a carbon nanotube / polyurethane solution, which is placed in a reagent bottle for later use;
[0088] (3) Preparation of highly durable superhydrophobic glass
[0089] a) Apply KH550 on the surface of the glass sheet with a thickness of 0.03mm;
[0090] b) Apply epoxy resin adhesive with a thickness of 0.2mm;
[0091] c) Use a micron-sized mesh to evenly disperse the carbon fiber micron particles on a glass sheet coated with epoxy resin adhesive to a thickness of 0.3 mm, and place it in an oven at 70°C for 2 hours;
[0092] d) Spraying carbon nanotube / polyurethane solution on carbon fiber micron particles with a thickness of 0.25 mm, drying in an oven at 70° C. for 2 h, and obtaining highly durable super-hydrophobic glass.
[0093] The contact angle test was performed on the highly durable super hydrophobic glass prepared in this embodiment. Figure 3-4 As shown, the measured contact angle is 152.6°. After the 5000g falling sand test, the contact angle is measured to be 146.1°.
[0094] Example 3
[0095] The preparation method of the highly durable super hydrophobic glass of the present embodiment comprises the following steps:
[0096] (1) Preparation of 22wt.% epoxy resin adhesive
[0097] Add 2.2 parts of epoxy resin to 7.6 parts of ethyl acetate, stir until dissolved, then add 0.2 parts of tetraethylene pentamine, stir until completely dissolved to obtain epoxy resin adhesive, put it into a reagent bottle for later use;
[0098] (2) Preparation of carbon nanotube / polyurethane solution
[0099] 1) Preparation of polyurethane prepolymer
[0100] 1.05 parts of TDI and 1.6 parts of HTPB were added to 25.25 parts of ethyl acetate, stirred evenly, and put into a flask, and then the flask was placed in an oil bath and stirred at 80°C. After prepolymerization for 1 hour, the flask was taken out and cooled to room temperature to obtain a polyurethane prepolymer;
[0101] 2) Preparation of carbon nanotube / polyurethane solution
[0102] Add 3.15 parts of carbon nanotubes to 15.75 parts of ethyl acetate, stir evenly, and mix evenly with polyurethane prepolymer to obtain a carbon nanotube / polyurethane solution, which is placed in a reagent bottle for later use;
[0103] (3) Preparation of highly durable superhydrophobic glass
[0104] a) Apply KH550 on the surface of the glass sheet with a thickness of 0.04mm;
[0105] b) Apply epoxy resin adhesive with a thickness of 0.3mm;
[0106] c) Use a micron-sized mesh to evenly disperse the carbon fiber micron particles on a glass sheet coated with epoxy resin adhesive to a thickness of 0.4 mm, and place it in an oven at 80°C for 1 hour;
[0107] d) Spraying carbon nanotube / polyurethane solution on carbon fiber micron particles with a thickness of 0.3 mm, drying in an oven at 80° C. for 1 h, and obtaining highly durable super-hydrophobic glass.
[0108] The contact angle test was performed on the highly durable super hydrophobic glass prepared in this embodiment. Figure 5-6 As shown, the measured contact angle is 159.5°. After the 5000g falling sand test, the contact angle is measured to be 152.1°.
[0109] Example 4
[0110] The preparation method of the highly durable super hydrophobic glass of the present embodiment comprises the following steps:
[0111] (1) Preparation of 20wt.% epoxy resin adhesive
[0112] Add 2 parts of epoxy resin to 7.82 parts of ethanol, stir until dissolved, then add 0.18 parts of triethylenetetramine, stir until completely dissolved to obtain epoxy resin adhesive, put it into a reagent bottle for later use;
[0113] (2) Preparation of carbon nanotube / polyurethane solution
[0114] 1) Preparation of polyurethane prepolymer
[0115] 1.05 parts of TDI and 3 parts of HTPB were added to 25.25 parts of ethanol, stirred evenly, and put into a flask, and then the flask was placed in an oil bath pot and stirred at 80°C. After prepolymerization reaction for 2 hours, the flask was taken out and cooled to room temperature to obtain a polyurethane prepolymer;
[0116] 2) Preparation of carbon nanotube / polyurethane solution
[0117] Add 4.2 parts of carbon nanotubes to 21 parts of ethanol, stir evenly, and mix evenly with polyurethane prepolymer to obtain a carbon nanotube / polyurethane solution, which is placed in a reagent bottle for later use;
[0118] (3) Preparation of highly durable superhydrophobic glass
[0119] a) Apply KH550 on the surface of the glass sheet with a thickness of 0.05mm;
[0120] b) Apply epoxy resin adhesive with a thickness of 0.2mm;
[0121] c) Use a micron-sized mesh to evenly disperse the carbon fiber micron particles on a glass sheet coated with epoxy resin adhesive to a thickness of 0.3 mm, and place it in an oven at 60°C for 1 hour;
[0122] d) Spraying carbon nanotube / polyurethane solution on carbon fiber micron particles with a thickness of 0.2 mm, drying in an oven at 60° C. for 1 h, and obtaining highly durable super-hydrophobic glass.
[0123] The contact angle test was performed on the highly durable super hydrophobic glass prepared in this embodiment. Figure 7-8 As shown, the measured contact angle is 153.1°. After the 5000g falling sand test, the contact angle is measured to be 146.4°.
[0124] Comparative Example 1
[0125] The difference from Example 2 is that in step d), the thickness of the sprayed carbon nanotube / polyurethane solution is 0.1 mm.
[0126] The contact angle test was performed on the glass prepared in Comparative Example 1. Figure 9-10 As shown, the measured contact angle is 146.3°. After the 5000g falling sand test, the contact angle is measured to be 142°.
[0127] Comparative Example 2
[0128] The difference from Example 2 is that in step d), the thickness of the sprayed carbon nanotube / polyurethane solution is 0.4 mm.
[0129] The contact angle test was performed on the glass prepared in Comparative Example 2. Figure 11-12 As shown, the measured contact angle is 146°. After the 5000g falling sand test, the contact angle is measured to be 142.3°.
[0130] When the coating formed by spraying carbon nanotube / polyurethane solution is too thick, the material will produce great internal stress during the curing process, thereby affecting the density of its rough structure and reducing the hydrophobicity of the material; at the same time, it will also reduce the adhesion of the coating to the base material, thereby significantly reducing its wear resistance.
[0131] Comparative Example 3
[0132] The difference from Example 1 is that in step c), the carbon fiber micron particles are evenly dispersed on a glass sheet coated with epoxy resin adhesive using a micron-grade mesh screen to a thickness of 0.5 mm, and then placed in an oven for drying at 60° C. for 1 hour.
[0133] The contact angle test was performed on the glass prepared in Comparative Example 3. Figure 13-14 As shown, the measured contact angle is 145.5°. After the 5000g falling sand test, the contact angle is measured to be 141.3°.
[0134] When the carbon fiber micron particle layer is too thick, internal stress will be generated when it is dried and cured together with the epoxy resin adhesive, resulting in defects inside the carbon fiber micron particle layer, thereby reducing its density, and affecting its adhesion to the base material, reducing the hydrophobicity and wear resistance of the material.
[0135] Comparative Example 4
[0136] The difference from Example 1 is that, in step 1), a polyurethane prepolymer is prepared: 0.52 parts of TDI and 4 parts of HTPB are added to 25.25 parts of ethyl acetate, stirred evenly, and put into a flask, and then the flask is placed in an oil bath and stirred at 80°C. After the prepolymerization reaction for 1 hour, the flask is taken out and cooled to room temperature to obtain a polyurethane prepolymer.
[0137] The contact angle test was performed on the glass prepared in Comparative Example 4. Figure 15-16As shown, the measured contact angle is 149.7°. After the 5000g falling sand test, the contact angle is measured to be 140°.
[0138] Comparative Example 5
[0139] The difference from Example 1 is that, in step 1), a polyurethane prepolymer is prepared: 3.15 parts of TDI and 4 parts of HTPB are added to 25.25 parts of ethyl acetate, stirred evenly, and put into a flask, and then the flask is placed in an oil bath and stirred at 80°C. After the prepolymerization reaction for 1 hour, the flask is taken out and cooled to room temperature to obtain a polyurethane prepolymer.
[0140] The contact angle test was performed on the glass prepared in Comparative Example 5. Figure 17-18 As shown, the measured contact angle is 143.5°. After the 5000g falling sand test, the contact angle is measured to be 139.5°.
[0141] The hard segment region of the polyurethane prepolymer tends to be arranged into crystals. The higher the hard segment content, the higher the strength, but the elongation and toughness decrease. The soft segment is in a disordered glass state. The higher the soft segment content, the higher the toughness and elasticity of the polyurethane prepolymer, but the hardness and mechanical properties decrease. The polyurethane chain segment is an island structure. Too high a hard segment content will lead to too many ordered regions, affecting the entanglement and interlocking of the polyurethane with the carbon nanotubes, and will also reduce the surface elasticity of the coating, thereby reducing the hydrophobicity and wear resistance of the coating; too high a soft segment content will lead to a decrease in the mechanical properties of the coating surface structure and a significant decrease in wear resistance, but it has little effect on the initial hydrophobicity.
[0142] Comparative Example 6
[0143] The difference from Example 1 is that, in step 2), a carbon nanotube / polyurethane solution is prepared: 5.25 parts of carbon nanotubes are added to 5.25 parts of ethyl acetate, stirred evenly, and then mixed evenly with a polyurethane prepolymer to obtain a carbon nanotube / polyurethane solution, which is then put into a reagent bottle for later use.
[0144] The contact angle test was performed on the glass prepared in Comparative Example 6. Figure 19-20 As shown, the measured contact angle is 142.5°. After the 5000g falling sand test, the contact angle is measured to be 138.5°.
[0145] Comparative Example 7
[0146] The difference from Example 1 is that, in step 2), a carbon nanotube / polyurethane solution is prepared: 0.52 parts of carbon nanotubes are added to 5.25 parts of ethyl acetate, stirred evenly, and then mixed evenly with a polyurethane prepolymer to obtain a carbon nanotube / polyurethane solution, which is then put into a reagent bottle for later use.
[0147] The contact angle test was performed on the glass prepared in Comparative Example 7. Figure 21-22As shown, the measured contact angle is 143.4°. After the 5000g falling sand test, the contact angle is measured to be 137.6°.
[0148] The mass ratio of carbon nanotubes and polyurethane hard segments should be controlled within a reasonable range. When the carbon nanotube content is too high, it is difficult for the carbon nanotubes to be entangled with polyurethane. When the polyurethane hard segment content is too high, the roughness of the entangled structure of carbon nanotubes and polyurethane will decrease, affecting the construction of the dual-scale rough structure.
[0149] Comparative Example 8
[0150] The difference from Example 1 is that step 2 is not performed, and in step d), a polyurethane solution is sprayed on the carbon fiber micron particles.
[0151] The contact angle test was performed on the glass prepared in Comparative Example 8. Figure 23-24 As shown, the measured contact angle is 144.5°. After the 5000g falling sand test, the contact angle is measured to be 140.7°.
[0152] In Comparative Example 8, no carbon nanotubes are added, and thus a double network interpenetrating structure cannot be formed together with polyurethane, which affects the wear resistance of the coating and the construction of a rough structure of nanometer size.
[0153] Comparative Example 9
[0154] The difference from Example 1 is that step 1 is not performed. Step 2) prepares a carbon nanotube dispersion: 1.05 parts of carbon nanotubes are added to 5.25 parts of ethyl acetate and stirred evenly to obtain a carbon nanotube dispersion, which is put into a reagent bottle for later use; in step d), the carbon nanotube dispersion is sprayed on the carbon fiber micron particles.
[0155] The contact angle test was performed on the glass prepared in Comparative Example 9. Figure 25-26 As shown, the measured contact angle is 137.5°. After the 5000g falling sand test, the contact angle is measured to be 130.5°.
[0156] In Comparative Example 9, no polyurethane is added, and thus a double network interpenetrating structure cannot be formed together with the carbon nanotubes, which affects the wear resistance of the coating.
[0157] Comparative Example 10
[0158] The difference from Example 1 is that step c) is not performed.
[0159] The contact angle test was performed on the glass prepared in Comparative Example 10. Figure 27-28 As shown, the measured contact angle is 136.9°. After the 5000g falling sand test, the contact angle is measured to be 130.8°.
[0160] In Comparative Example 10, carbon fiber micron particles are not added, so a dual-scale rough structure cannot be constructed with carbon nanotubes / polyurethane, thereby reducing the wear resistance and hydrophobic properties of the glass hydrophobic surface.
[0161] Comparative Example 11
[0162] The difference from Example 1 is that in step (2), the Poss / organic silicone solution is prepared by taking 2 parts of Poss (polyhedral oligomeric silsesquioxane) and 1 part of addition-type liquid silicone rubber, adding 12 parts of ethyl acetate and 0.09 parts of tetraethylenepentamine, and fully dissolving them to obtain a Poss / organic silicone solution; in step d), the Poss / organic silicone solution is sprayed on the carbon fiber micron particles.
[0163] The contact angle test was performed on the glass prepared in Comparative Example 11. Figure 29-30 As shown, the measured contact angle is 146.2°. After the 5000g falling sand test, the contact angle is measured to be 141.5°.
[0164] Poss and silicone form a semi-interpenetrating network structure, and the double-network interpenetrating structure formed by polyurethane and carbon nanotubes in the present invention has a higher roughness and stronger mechanical properties than the semi-interpenetrating network structure in that the rough structure of nanoscale size is constructed; at the same time, compared with Poss, the polyurethane used in the present invention has an island structure constructed by soft segments and hard segments, and has better mechanical properties. The combination of carbon nanotubes and polyurethane also has better mechanical properties than the combination of Poss / silicone.
[0165] Comparative Example 12
[0166] The difference from Example 1 is that in step 2), Poss is used in equal amount to replace carbon nanotubes to obtain Poss / polyurethane solution; in step d), Poss / polyurethane solution is sprayed on carbon fiber micron particles.
[0167] The contact angle test was performed on the glass prepared in Comparative Example 12. Figure 31-32 As shown, the measured contact angle is 145.9°. After the 5000g falling sand test, the contact angle is measured to be 142.9°.
[0168] The combination of Poss and polyurethane cannot form an entangled and interlocking double network interpenetrating structure, and the hydrophobicity and wear resistance are relatively poor.
[0169] Comparative Example 13
[0170] The difference from Example 1 is that in step 1), 5.05 parts of addition-type liquid silicone rubber are added to 12 parts of ethyl acetate, and then 0.09 parts of tetraethylenepentamine are added and fully dissolved to obtain an organosilicon solution; in step 2), 1.05 parts of carbon nanotubes are added to 5.25 parts of ethyl acetate, stirred evenly, and then mixed evenly with the organosilicon solution to obtain a carbon nanotube / organosilicon solution, which is put into a reagent bottle for standby use; in step d), the carbon nanotube / organosilicon solution is sprayed on the carbon fiber micron particles.
[0171] The contact angle test was performed on the glass prepared in Comparative Example 13. Figure 33-34 As shown, the measured contact angle is 145.8°. After the 5000g falling sand test, the contact angle is measured to be 140.6°.
[0172] Silicone cannot form an entangled and interlocked double network interpenetrating structure with carbon nanotubes, resulting in relatively poor hydrophobicity and wear resistance of superhydrophobic glass.
Claims
1. A method for preparing highly durable super-hydrophobic glass, characterized in that: The following steps are involved: (1) Preparation of epoxy resin adhesive Adding epoxy resin to an organic solvent and stirring until dissolved, adding a curing agent and stirring until dissolved to obtain an epoxy resin adhesive; (2) Preparation of carbon nanotube / polyurethane solution 1) Preparation of polyurethane prepolymer Toluene diisocyanate and hydroxyl-terminated liquid polybutadiene rubber are added to an organic solvent, prepolymerized at 60-80°C for 1-2 hours, and then cooled to room temperature to obtain a polyurethane prepolymer, wherein the mass ratio of the soft segment to the hard segment of the polyurethane prepolymer is 3:(1-2); 2) Preparation of carbon nanotube / polyurethane solution Adding carbon nanotubes to an organic solvent, and then adding the organic solvent to the polyurethane prepolymer prepared in step 1), mixing evenly, to obtain a carbon nanotube / polyurethane solution, wherein the mass ratio of the carbon nanotubes to the hard segment in the polyurethane prepolymer is (1-4):1; (3) Preparation of highly durable superhydrophobic glass a) Apply surfactant on the surface of the glass sheet; b) brushing the epoxy resin adhesive prepared in step (1) on the surfactant; c) using a micron-sized mesh screen to evenly disperse the carbon fiber micron particles on a glass sheet coated with an epoxy resin adhesive, and drying, wherein the thickness of the carbon fiber micron particles on the glass sheet is 0.2-0.4 mm; d) spraying the carbon nanotube / polyurethane solution prepared in step (2) onto the carbon fiber micron particles to a thickness of 0.2-0.3 mm, and drying to obtain a highly durable super hydrophobic glass.
2. The method for preparing a highly durable super-hydrophobic glass according to claim 1, wherein: In step (1), the concentration of epoxy resin in the epoxy resin adhesive is 18-22 wt.%, and the concentration of curing agent is 1.6-2 wt.%.
3. The method for preparing a highly durable super-hydrophobic glass according to claim 1, wherein: In step (1) and step (2), the organic solvent is ethyl acetate or ethanol, and the curing agent is tetraethylenepentamine or triethylenetetramine.
4. The method for preparing a highly durable super-hydrophobic glass according to claim 1, wherein: In step a), the surfactant is KH550.
5. The method for preparing highly durable super hydrophobic glass according to claim 1, wherein: In step a), the thickness of the surfactant brushed on the glass sheet is 0.02-0.05 mm.
6. The method for preparing the highly durable super-hydrophobic glass according to claim 1, wherein: In step b), the thickness of the epoxy resin adhesive applied on the glass sheet is 0.1-0.3 mm.
7. The method for preparing the highly durable super-hydrophobic glass according to claim 1, wherein: In step c) and step d), the drying temperature is 60-80° C. and the drying time is 1-3 hours.
8. Highly durable super hydrophobic glass, characterized in that: The highly durable super hydrophobic glass is prepared by the method for preparing the highly durable super hydrophobic glass as described in any one of claims 1 to 7.
Citation Information
Patent Citations
Preparation method of fluorinated halloysite nanotube / waterborne polyurethane composite hydrophobic coating layer
CN108977030A
Epoxy resin-based super-hydrophobic nano composite coating and preparation method thereof
CN118027782A